A comparative evaluation of migration sedimentation method for sperm preparation. (4th March 2018) - Kiratli, Sevil; Yuncu, Mehmet; Kose, Kenan; Ozkavukcu, Sinan
ABSTRACT: The effectiveness of semen preparation using the migration-sedimentation (MS) method was evaluated, and compared to density gradient centrifuge and swim-up combination (DGC+SU). Sperm selection using MS is based on motility, thus, deleterious effects for which centrifugation has been blamed, are believed to be avoided. Normozoospermic male patients who had more than 10% forward progressive motile sperm in their ejaculate were included in the study. Spermatozoa selected by two different methods were investigated and compared according to sperm motility, concentration, morphology, vitality, DNA fragmentation, and presence of persistent histones. The concentration and motility of sperm in the MS group was improved when compared to the DGC+SU group, but the difference between groups was not significant. The proportion of sperm with normal morphology was found to be 12.19 ± 6.45% vs. 10.67 ± 5.44%, vitality rate was 74.09 ± 16.65% vs. 70.45 ± 16.78%, DNA fragmentation rate was 3.91 ± 3.96%, vs. 2.95 ± 3.33%, presence of persistent histone proportion was 10.59 ± 13.40%, vs. 8.86 ± 7.89% in DGC+SU and MS groups respectively, without significance. The simple technique avoids centrifuge-based damage.